Peran Motivasi dan Kepuasan Kerja dalam Optimalisasi Kinerja Sumber Daya Manusia pada PT Arat Arta Valuta - Heni Kesumayani (MAMEN: Jurnal Manajemen, 2025)
In a competitive business landscape, human resources are a primary driver of organizational excellence. This study investigates the influence of work motivation—measured through the fulfillment of physiological needs, security, and self-actualization—on employee performance at PT Arat Arta Valuta, with job satisfaction positioned as a mediating variable. A descriptive quantitative method was employed, collecting primary data through questionnaires from 40 employees. The analysis confirms that work motivation has a significant and direct positive effect on improving performance (assessed based on work quality, timeliness, and attendance). Furthermore, the findings reveal that this influence also operates indirectly through enhanced job satisfaction, which was evaluated based on intrinsic aspects of the work, compensation, promotion opportunities, and interpersonal relationships. The implications of this research affirm that creating a holistic work environment—which integrates the fulfillment of basic needs with recognition and opportunities for self-development—is key to building superior and sustainable performance. Therefore, management is encouraged to shift from an approach focused solely on production means towards a humane and empowering human resource management strategy, where motivation and job satisfaction become central pillars.